IMPLEMENTASI PENDEKATAN PRAGMATIK DALAM PEMBELAJARAN KETERAMPILAN BERBICARA DI SEKOLAH - Muh Jaelani Al-Pansori (Universitas PGRI Madiun, 2014)
This article is a theoretical study on the implementation of a pragmatic approach in learning speaking skills at school. Pragmatic approach is one of learning approaches that aims to train students to improve their speaking skills at school. This approach focuses on contextual learning speaking skills, particularly in the process of learning at school. Through this approach, students will be brought closer to practical conditions of speaking both orally and in writing. Thus, the learning skills of speaking with a pragmatic approach are very effective in creating active learning, especially in improving their speaking ability in the classroom and outside the classroom. Keywords: pragmatic approach, speaking skills